2019
DOI: 10.1504/ijwoe.2019.106892
|View full text |Cite
|
Sign up to set email alerts
|

Psychological capital, task autonomy and innovative work behaviour among public organisation employees

Abstract: A fierce competitive workplace climate compels employees to work under pressure, hence, to perform requires individual's innovate positive psychological resources. This paper sets out to examine the predictive relationship between psychological capital (PsyCap) and innovative work behaviour (IWB) among public employees, and the role of task autonomy in the relationship. A cross-sectional survey design was conducted, and 125 employees from public hospitals participated in the study. The study used a questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Research on trust in leadership has not been done much, from the results of this study it is known that trust in leader is a factor that influences IWB both as an independent variable [ 23 ] and mediation [ 23 , 63 ] as well as moderator [ 40 ]. Team works support also serves as a moderator for IWB in public organizations [ 17 , 66 ], which means that support from colleagues will strengthen IWB.…”
Section: Resultsmentioning
confidence: 99%
“…Research on trust in leadership has not been done much, from the results of this study it is known that trust in leader is a factor that influences IWB both as an independent variable [ 23 ] and mediation [ 23 , 63 ] as well as moderator [ 40 ]. Team works support also serves as a moderator for IWB in public organizations [ 17 , 66 ], which means that support from colleagues will strengthen IWB.…”
Section: Resultsmentioning
confidence: 99%
“…According to Fredrickson's (2013) expand-and-build theory, positive emotions expand thought-action repertoires and originate an accumulation of resources, available to the individual, so that a high PsyCap would increase innovative behaviors, due to a greater capacity to combine thoughts and ideas (Luthans et al, 2011). Thus, PsyCap would be positively related to creative performance (Ozturk & Karatepe, 2019), creativity (Cai et al, 2019) and innovative work behavior (Abbas & Raja, 2015;Nwanzu & Babalola, 2019;Paul & Devi, 2018). The scientific community is responding to the call for research on PsyCap and its influence on innovative work behavior, and multilevel research is emerging, providing further insight into the relationship of team PsyCap (Uen et al, 2021) and leader PsyCap (Wang et al, 2021), on individual-level employee innovative behavior, resulting in positive findings in both studies.…”
Section: Psycap and Innovative Work Behaviormentioning
confidence: 99%
“…PsyCap is an essential predictor of desirable work-related attitudes and behaviors such as satisfaction, psychological well-being (Hmieleski and Carr, 2007; Yu et al , 2019 Uen et al , 2021). Employees with high PsyCap are considered forthright enough to speak up to have positive outcomes (Luthan et al , 2006; Nwanzu and Babalola, 2019). EVB is considered a constructive behavior because it enhances the current situation by sharing, participating and advising as required (Turnley and Feldman, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Uen et al (2021) suggested that identifying opportunities and exploration is possible in a positive work environment. Scholars (Axtell et al, 2000;Nwanzu and Babalola, 2019) found a positive relationship between proactive behavior like taking charge and self-efficacy on personal initiatives for idea generation. Employees who are optimistic about the innovative steps taken and their outcomes can demonstrate IWB (Axtell et al, 2000;Nwanzu and Babalola, 2019).…”
Section: Psychological Capital and Employee Voice Behaviormentioning
confidence: 99%
See 1 more Smart Citation